2004
DOI: 10.1021/ma0359584
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Utilization of Catalyst-Functionalized Single-Walled Carbon Nanotubes for Ring-Opening Metathesis Polymerization

Abstract: Single-walled carbon nanotubes were oxidatively shortened and functionalized with ruthenium-based olefin metathesis catalysts. These catalyst-functionalized nanotubes were shown to be effective in the ring-opening metathesis polymerization of norbornene, resulting in rapid polymerization from the catalyst sites on the nanotube. It was found that high polymer molecular weights could be reached, and the molecular weight increased linearly with polymerization time. The resulting polynorbornene-functionalized nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 28 publications
2
58
1
3
Order By: Relevance
“…1a), there was no weight loss even up to 800°C whereas in MWCNTs-COOH (Fig. 1b), 3% weight loss was observed and this is due to the decomposition of carboxyl groups from 300 to 500°C [50,51]. A similar study has already been reported for the decomposition of poly(amidoamine) dendrimers at 200-400°C.…”
Section: Resultssupporting
confidence: 80%
“…1a), there was no weight loss even up to 800°C whereas in MWCNTs-COOH (Fig. 1b), 3% weight loss was observed and this is due to the decomposition of carboxyl groups from 300 to 500°C [50,51]. A similar study has already been reported for the decomposition of poly(amidoamine) dendrimers at 200-400°C.…”
Section: Resultssupporting
confidence: 80%
“…The surface modification generally involves attaching functional groups to CNTsurfaces through the formation of covalent bonds (covalent approaches) or non-covalent bonds (non-covalent approaches). Although the covalent approach [4][5][6][7][8][9][10][11][12] is efficient in functionalizing CNTs, the covalent bonding inevitably disrupts the long range p conjugation of CNTs, leading to decreased electrical properties and diminished mechanical strength. On the other hand, non-covalent approach utilizes the multiple weak interactions such as p-p interactions, [13][14][15][16][17][18][19][20][21][22] van der Waals interactions, [23,24] and static charge interactions.…”
Section: Introductionmentioning
confidence: 99%
“…reported Grubbs' catalyst grafted single-walled carbon nanotubes using ROMP of norbomene and proposed that those functionalized catalysts on the surface of the nanotube can be used as rapid polymerization sites but bulk composites were not reported [39]. The second approach is kinetically favorable but statistically less likely due to the excess DCPD The increased elongation of f-MWCNT/polyDCPD nanocomposites could be due to several toughening mechanisms.…”
Section: Resultsmentioning
confidence: 99%